Analogy between Immune System and Sensor Replacement Using Mobile Robots on Wireless Sensor Networks - Watanabe, Yuji; Jyo, Ei (Procedia Computer Science, 2014)
In wireless sensor networks, sensor nodes with dead battery make holes in sensing coverage. It is necessary to fill the holes by replacing the nodes of dead battery with fully-charged ones. This is called sensor replacement. In this paper, following the existing study, to clarify the distribution of nodes information to robots, we propose two centralized manager algorithms where repairing robots have or not have the information list of nodes with dead battery. We carry out some simulations under the constant density of nodes per robots and then clarify the tradeoff between the messaging overhead and the motion overhead. We also investigate the case of the limited energy of the robots. Finally, we discuss the analogy between immune system and sensor replacement using mobile robots.